2017
DOI: 10.1002/admi.201700737
|View full text |Cite
|
Sign up to set email alerts
|

Octahedral Distortions at High‐Temperature Superconducting La2CuO4 Interfaces: Visualizing Jahn–Teller Effects

Abstract: properties of complex perovskite oxide structures are strongly influenced by small structural changes of the BO 6 octahedral network. [2][3][4][5] Impressive examples are heterostructure interfaces for which even small alterations of the octahedral network can give rise to striking changes in the electronic structure [6,7] and induce functional properties such as quantum Hall effect, [8] magnetism, [9] superconductivity, [10,11] ferroelectricity, [12] the formation of 2D free electron gases, [13] and hightempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 55 publications
0
19
0
Order By: Relevance
“…As a matter of fact, certain intermixing is often observed, but its width and its effect on the system properties (being arguably dependent on the deposition process) are in many cases still under debate. 31,[45][46][47] Our case is particularly interesting since it exhibits an asymmetric behavior for the two interfaces, whose intermixing width depends on the layer sequence. Such a finding has been highlighted in the case of epitaxial semiconducting structures (cf.…”
Section: Discussionmentioning
confidence: 97%
“…As a matter of fact, certain intermixing is often observed, but its width and its effect on the system properties (being arguably dependent on the deposition process) are in many cases still under debate. 31,[45][46][47] Our case is particularly interesting since it exhibits an asymmetric behavior for the two interfaces, whose intermixing width depends on the layer sequence. Such a finding has been highlighted in the case of epitaxial semiconducting structures (cf.…”
Section: Discussionmentioning
confidence: 97%
“…In addition to above-mentioned research, we further utilized the advantages of the layer-by-layer MBE technique. Bauitti et al [105] reported a new approach for the design of epitaxially grown HTS of cuprates and showed that when twodimensional doping, i.e., δ-doping, which is the substitution of a selected La-O layer with a Sr-O layer during the epitaxial growth, is applied to the LCO matrix, an asymmetric The La 2 CuO 4 structure forms a pseudo-tetragonal structure when grown on LaSrAlO 4 substrates [92,93] distribution of the dopant is present [105,106]. For such type of doping, the asymmetric dopant distribution profile generates two different types of HTS mechanisms at each side of the interface.…”
Section: Homo-epitaxy and Ht-is Of La 2 Cuomentioning
confidence: 99%
“…5c) turns into a conventionally doped LCO system and most of the layers were found to be superconducting. Furthermore, when the local octahedral distortions, i.e., apical O-O interatomic distances, are quantitatively investigated and associated with the dopant distributions, the correlation with local Jahn-Teller distortions is enlightened [93]. While in the case of sharp interfaces (i.e., Ca and Sr doping), the O-O interatomic distances increase sharply after the nominal M-I interface, anti-Jahn-Teller distortions dominates the structure for Ba doping due to the wide Ba distribution leading to a reduction of the apical O-O interatomic distances [109].…”
Section: Homo-epitaxy and Ht-is Of La 2 Cuomentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, interface engineering is an intriguing yet challenging task and the atomically precise design of complex oxide heterostructures requires atomic-resolution identification of individual layers and interfaces (Figure 3). The prominent role is played by aberration-corrected scanning transition electron microscopy (STEM) with high-resolution imaging and spectroscopy capabilities [14,15]. STEM high-angle annular dark field (HAADF) images of three different La 2 CuO 4 -based heterostructures are presented in Figure 3a-c [6] displaying the ideally arranged crystal structure without any extended defects.…”
mentioning
confidence: 99%